Pemantauan Kualitas Udara Laboratorium Berbasis IOT dan ESP8266 - Agung Wibawa (Jurnal Publikasi Teknik Informatika, 2025)
The air quality in the laboratory plays a crucial role in ensuring health and safety, especially in enclosed environments that are susceptible to the accumulation of pollutants such as CO₂ and dust particles. This research aims to design and implement an Internet of Things (IoT)-based air quality monitoring system using the NodeMCU ESP8266 microcontroller, MQ-135 sensor, and GP2Y1010AU0F, which can detect harmful gases and dust particles in real time. A systems engineering approach was applied, from observing the needs in the Pertamina Central Hospital laboratory and prototyping to performance testing of the system over seven days with automatic data collection via WiFi and Laravel-based web visualization. The study results indicate that the system can detect fluctuations in air quality with high accuracy, provide early warnings through a buzzer when threshold limits are exceeded, and present data in real time through a dashboard. In conclusion, this system offers practical contributions through a cost-effective and easy-to-implement monitoring solution. It strengthens the theoretical foundations in applying IoT technology for effectively and responsively managing laboratory air quality.